Effect of some formulation additives on the oral, absorption of indomethacin - Pandit J.K.; Jagadeesh G.; Nagabooshanam M.; Tripathi M.K. (My University, 2025)
Higher dissolution rates of indomethacin were noted in glycerin-water mixtures, sucrose solutions, sod.-cmc mucilage, from a fabricated capsule containing a buffer and also from drug crystals obtained by precipitation in presence of a physiological surfactant solution. Dogs fed with the drug along with these additives and in the form of a lipid-containing dosage form shoved significantly increased plasma-indomethacin levels. The magnitude of plasma-drug levels from aqueous and oily suspensions and from the prepared capsule was found to be significantly greater than that obtained from the marketed preparation. © 1984 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.